The basis for setting aside a three-party bank-lending transaction entered into by ‘Undue Influence’ under Section 16 of the Malaysia Contracts Act 1950: A grey area of laws - Noor Inayah Yaakub (Fakulti Undang - Undang, 2005)

(untitled)
One of the grey areas of law with regards to the law of undue influence in a three-party situation in Malaysia is its basis for setting aside a transaction. Since the word ‘unconscionable’ is not defined in the Contracts Act 1950, it is unclear from this subsection whether Malaysian courts would grant relief to a claimant not on the sole ground of undue influence but also on the proof of unconscionability. The main aim of this paper is to explain what is the actual basis in Malaysia for setting aside a bank-lending transaction entered into by undue influence